Social Factors Of Organization And Management Of Student Sports Training - Akhmadova Charos Bakhtiyar qizi (Peerian Journals Publishing, 2023)
This article reveals the social implications of physical education and mass sports. A different approach assesses the social essences of sports, points out ways to improve the organization, and conducts various activities among different segments of the population, including youth.
Keywords: students; physical education; mass sports